Functional analysis of PCSK2 coding variants: A founder effect in the Old Order Amish population. (September 2017) - Winters, Alexandra; Ramos-Molina, Bruno; Jarvela, Timothy S.; Yerges-Armstrong, Laura; Pollin, Toni I.; Lindberg, Iris
Highlights: The PCSK2 coding variant R430W is greatly enriched in the Old Order Amish population. The R430W variant is twice as common among Old Order Amish individuals with T2D. The R430W substitution results in a broader pH range of enzyme activity. The rare coding variant A267T is not secreted. Abstract: Aims: In humans, noncoding variants of PCSK2, the gene encoding prohormone convertase 2 (PC2), have been previously associated with risk for and age of onset of type 2 diabetes (T2D). The aims of this study were to identify coding variants in PCSK2 ; to determine their possible association with glucose handling; and to determine functional outcomes for coding variants in biochemical studies. Methods: Exome-wide genotyping was performed on 1725 Old Order Amish (OOA) subjects. PCSK2 coding variants were tested for association with diabetes-related phenotypes. In vitro analyses using transfected human PC2-encoding constructs were performed to determine the impact of each mutation on PC2 activity. Results: We identified 10 rare missense coding variants in PCSK2 in various genomic databases. R430W (rs200711626) is greatly enriched in the OOA population (MAF 4.3%). This variant is almost twice as common (MAF 7.4%) in OOA individuals with T2D as in OOA individuals with normal or with normal/impaired glucose tolerance (MAF 3.9% and 2.9%, respectively; p = 0.25 and p = 0.10). In vitro experiments revealed a broadening of the pH optimum for the R430W variant, which may result in increased activity against PCSK2 substrates. Conclusions: Although the association of the R430W variation with T2D in the OOA population did not reach significance, based upon the broadened pH profile of R430W PC2, we speculate that the presence of this substitution may result in altered processing of PCSK2 substrates, ultimately leading to increased conversion to diabetes.